Short film versus spot: cinematographic influence on John-Lewis & Partners Advertising - Cea Navas, Ana Isabel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The cinema-advertising influence has been studied: Cuadrado (2007) investigates both disciplines in digital technology; Jiménez and García (2011, 2012) analyze intertextuality on television or in specific creations (Mercedes class C). Applying a content analysis methodology, we intend to show this synergy, examining the promotional advertisements of the company John Lewis & Partners. Evaluating the script of these creations, we will verify that most of these spots have been elaborated following the paradigm of Syd Field, adjusting to the classic structure of construction of a story divided into three acts (approach-knot-end). Arguing, consequently, that these advertising tapes are short films.